Implementation of E-Voting in The Election of The OSIS Chairman of Smkn 2 Rancaekek - Muhamad Ramadan; Damai Saputra Laoli; Muhammad Rifqu Abdillah (International Journal of Research and Applied Technology (INJURATECH), 2022)
In a school organization called OSIS, in general, there must always be a leader or can be called the chairman of the organization, there is an OSIS organization chairman, which aims to promote and prosper the organization in junior high schools and vocational schools, they also must have leadership structures and when We need a leader who deserves to be elected. Therefore This study aims to implement E- VOTING in the selection of student council leaders at SMKN 2 RANCAEKEK because some of the schools are still elected directly or can also be called by voting using paper. To support the research, we use the waterfall method of software development. The sequence in the waterfall method is very serial starting from the planning process of analysis, design, and implementation of the system. results show that election chairman OSIS this use Besides Fulfill principles, we must follow development technology Information as well as speed up the results of the vote recapitulation. Electronic voting or E-Voting is something from collection voice which normally used election general using electronic media. E-Voting also makes elections easierfor example: no eat the cost, speeds up recapitulation voice, honest, fair, happening transparency, and reduces fraud. Because that paper, discusses the application of E- Voting if it is applied to the field of school organization, namely in schools Vocational High School 2 RANCAEKEK.